The power of politics: selective exposure and social identity cues - Rizzuti, Noel T. (Kansas State University, 2014)
The objective of this study is to shed light on the interaction between the theory of selective exposure and social identity theory. Both of these theories describe aspects regarding how individuals expose themselves to information. However, the driving question of the study was to investigate the behavior of individuals whom experience cognitive dissonance from an inconsistent political message, but are receiving that message from a member of their perceived in-group. The expectation was that moderating variables, such as strength of identification with an ideology as well as the level of knowledge would impact who would engage in selective exposure and choose to disregard in-group cues, or choose inconsistent messages to stay true to in-group pressures. In a Qualtrics experiment, participants (n=189) were divided into different groups, attitude consistent and attitude inconsistent and were exposed to a series of tweets. Each tweet was politically charged, with the attitude-consistent group presenting consistent messages paired with in-group cues, and in the attitude-inconsistent group presenting a dissonant message was paired with the in-group cue, and visa versa. Two factors revealed themselves to impact results and message choice — knowledge and strength of identification. Results revealed that individuals who had a high level of knowledge chose the consistent message more often than those with low knowledge. The strength of ideology variable influenced differences in both the speed in which they made decisions on which tweet to select, as well as how quickly they identified with an ideology level. This result revealed that those who are strongly identified with an ideology make decisions regarding political messages and ideology faster than those who are weakly identified. The current study contributes to the plethora of literature regarding these two theories and the political science area of study by supporting knowledge as a moderating variable between cognitive dissonance and social identity pressures. It also provides insight into the trends and patterns that can arise when time/speed are utilized as a variable to shed light on group identification differences. The insights with the variables of time, strength of ideology, level of knowledge, could lead to numerous future studies.
Keywords: Political behavior; selective exposure; social identity cues; Twitter usage; social media; Psychology, Behavioral (0384)